Adapting the Material Circularity Indicator to evaluate circularity in food systems: two case studies on livestock rearing - Francesco Caraceni; Matteo Cordara; Carlo Brondi; Andrea Ballarino (Environmental and Sustainability Indicators)
In light of the growing interest in circular bioeconomy issues, this study aims to present an adaptation of the Material Circularity Indicator (MCI) for the quantitative assessment of circularity in agri-food systems. Specifically, the adapted MCI (a-MCI) developed in this research is designed to evaluate meat production in industrial farming. This is achieved by incorporating parameters such as the Survival Rate (SR) and the Feed Conversion Ratio (FCR) into the calculation of the utilisation factor (X) already embedded in the original MCI framework. The a-MCI's application was tested using case study data from various animal species (e.g., broilers and pigs), with the latter exhibiting a slightly higher a-MCI in the analysed case studies. Nonetheless, the significant variability of data collected from literature sources lead to results inconsistency, as the small sample of data induce a relevant standard deviation.